PECULIARITIES OF HEALTHCARE SPECIALISTS’ COMMUNICATIVE COMPETENCE IN ENGLISH AS A FOREIGN LANGUAGE - Pašinska, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Healthcare specialists are expected to possess competences essential for a successful fulfilment of their duties. Although specialists’ practical competences enabling them to deal with a wide range of health conditions are the key ones, communicative competence, implying an ability to use a target language “accurately, appropriately, and flexibly” (Yule, 2010, p.194), has also had an immense impact on the accomplishment of professional duties (World Health Organisation, 2005). It follows that apart from giving opportunities to acquire knowledge about medicine and practical skills, medical education institutions are expected to teach 21st century students to communicate effectively using various linguistic tools applicable in their professional context (Zethsen and Askehave, 2006). The present article aims to elucidate the peculiarities of communicative competence that practising or future healthcare providers should possess in order to demonstrate how it enables them to accomplish their responsibilities by communicating with patients and, thus, provide them with qualitative care or treatment in a foreign language, specifically English as a foreign language. With the aim to reach the goal, a scientific literature review was conducted. The theoretical implications were supported by the examples of medical encounters; in the given encounters, the use of the selected language aspects and participants’ non-verbal cues were interpreted.